The Effects of Peer Education Program Implemented by Nursing Students on the Beliefs of University Students towards the Mental Illness - Figen Şengün İnan; Neslihan Günüşen; Sevecen Çelik İnce; Zekiye Çetinkaya Duman (Dokuz Eylul University, 2020)
Background: Studies show that young adults as well as adults have negative attitudes towards people with mental illness. In addition, most mental illnesses begin in the youth and psychiatric help may be delayed due to stigmatization. At this point, it is important to turn the negative beliefs of young people towards mental illnesses into positive. Objectives: The aim of this study is to investigate the effects of peer education program by nursing students on the beliefs of university students towards mental illness. Methods: This study was carried out a single group with pre-test-post-test, quasi-experimental design. Study sample consisted of the university students from other departments than nursing (n: 144). Peer educators implemented a peer education program that aim combating stigma towards mental illnesses. During the data collection socio-demographic data collection form and Beliefs toward Mental Illness Scale were used. Data were collected before and after the peer education. Results: The mean scores of post-test for incurability and disturbance in interpersonal relationships, dangerousness, and shame subscales is statistically significantly lower than the mean scores of pre-test (p = .001). Conclusion: It was found that peer education program implemented by nursing students positive effects on the university students' beliefs towards mental illness. In this regard, peer education may be thought as a method for combating stigma towards the mental illness. It is recommended to investigate the effectiveness of peer education with a control group and longitudinal design.